Laboratory investigation of Parabens - Masse, Guillaume; Belt, Simon (The University of Hull)
This is a laboratory-based investigation of preservative chemicals commonly found in household products - parabens. Students carry out extractions of parabens froma product of choice and analyse the extracts using either GC or HPLC. Suggested methods are given for each analytical method. Composition data are compared against EU legislation for the use of parabens.